2009
DOI: 10.1007/s10657-009-9123-9
|View full text |Cite
|
Sign up to set email alerts
|

Judges as satisficers: a law and economics perspective on judicial liability

Abstract: Bounded rationality, Judicial errors, Civil, disciplinary and penal liability, Political accountability, Criteria for decision-making under risk and uncertainty, K13, K40, J41, D8,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
6
0
1
Order By: Relevance
“…Thus, the Sharia has become a part of Greek law although it is only applicable to some 100,000 Greek nationals. 72 However, the decisions of the mufti do not have res judicata effect and are only enforceable after a decision of the Greek court. 73 In the so-called Borrás Report it has been indicated that Brussels II bis is only applicable to civil proceedings and all merely religious proceedings are excluded from its scope.…”
Section: Findings/results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the Sharia has become a part of Greek law although it is only applicable to some 100,000 Greek nationals. 72 However, the decisions of the mufti do not have res judicata effect and are only enforceable after a decision of the Greek court. 73 In the so-called Borrás Report it has been indicated that Brussels II bis is only applicable to civil proceedings and all merely religious proceedings are excluded from its scope.…”
Section: Findings/results and Discussionmentioning
confidence: 99%
“…71 Many of these lawsuits were filed in 2007 and 2008 after the -global credit crisis.‖ In the trial of these lawsuits, courts have broken through previous barriers (such as the CRAs' use of the defences of press privilege and pure opinion) in imposing liability for ratings. 72 In 2013, Department of Justice (DOJ) sued Standard & Poor's for fraud. S&P reached a settlement with DOJ to pay USD1.375 billion.…”
Section: Common Themes and Recent Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, women who do not reach a settlement with their husband are more likely to remain in a non-functioning marriage. 63 In this respect, the economic imperative seems to operate as a suspensory factor and the described type of divorce is being transformed into a system of discouragement for Muslim minority women.…”
Section: Islamic Divorcementioning
confidence: 99%